Prospective Trial Evaluating the Surgical Anastomosis at One-Year Colorectal Cancer Surveillance: CT Colonography Versus Optical Colonoscopy and Implications for Patient Care. Issue 11 (November 2017) - Pickhardt, Perry J.; Edwards, Kristin; Bruining, David H.; Gollub, Marc; Kupfer, Sonja; Lubner, Sam J.; Kim, David H.; Ross, Eric; Keenan, Eileen; Weinberg, David S.
Abstract : OBJECTIVE: The aim of this study was to compare the accuracy of CT colonography versus optical colonoscopy for neoplastic involvement at the surgical anastomosis 1 year after curative-intent colorectal cancer resection. DESIGN, SETTING, PATIENTS, AND INTERVENTIONS: Two hundred one patients (mean age, 58.6 years; 117 men, 84 women) underwent same-day contrast-enhanced CT colonography and colonoscopy approximately 1 year (mean, 12.1 months; median, 11.9 months) after colorectal cancer resection as part of a prospective, multicenter trial. All patients enrolled were without clinical evidence of disease and considered low risk for recurrence (stage I–III). MAIN OUTCOME MEASURES: Suspected neoplastic lesions within 5 cm of the colonic anastomosis were recorded at CT colonography, with subsequent colonoscopy performed for the same, with segmental unblinding of colonography findings. Anastomotic region biopsy or polypectomy was performed at the endoscopist's discretion. RESULTS: None of the 201 patients had intraluminal anastomotic cancer recurrence or advanced neoplasia (or metachronous cancers). CT colonography detected extramural perianastomotic recurrence in 2 patients (1.0%); neither was detected at colonoscopy. Only 2 patients (1.0%; 2/201) were called positive at CT colonography for intraluminal anastomotic nondiminutive lesions (7- to 8-mm polyps), which were confirmed at colonoscopy but nonneoplastic at histopathology. At optical colonoscopy, the anastomosis was deemed abnormal and/or biopsied in 10.0% (20/201), yielding only 1 nondiminutive benign neoplasm (7-mm tubular adenoma). LIMITATIONS: The lack of luminal cancer recurrence in our lower-risk cohort precludes assessment of sensitivity for detection, rendering the study underpowered in this regard. Potential cost savings of combined CT/CT colonography over the standard CT/colonoscopy approach were not assessed. CONCLUSIONS: Relevant intraluminal anastomotic pathology appears to be very uncommon 1 year after colorectal cancer resection in lower-risk cohorts. Unlike colonoscopy, diagnostic contrast-enhanced CT colonography effectively evaluates both the intra- and extraluminal aspects of the anastomosis. SeeVideo Abstract athttp://links.lww.com/DCR/A471 .